A Reflection Study on Language Choices among Multilingual - Baiq Raudatul Jannah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2025)
Multilingual community is commonly found in Asian countries. Since people are able to communicate using more than one language, some factors may influence them in their language choices. This research was a reflection study in which the researcher herself became the participant of this research. Some factors that might influence the language choice was the interlocutors, the setting, and the language that the participant grew up with. During the conversation code-switching and code-mixing were also found since the speakers in the setting of research were also bilingual or multilingual.